Pengaruh Disiplin Kerja Dan Kepuasan Kerja Terhadap Kinerja Karyawan Pada PT. Pustaka Gemilang Motor - Lutfiah, Sari; Nurvi Oktiani (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
The purpose of this research is to find out how job satisfaction and work discipline impact the performance of PT employees. Gemilang Motor Library. This research uses quantitative methods. This research involved 30 employees in the human resources division of PT. Gemilang Motor Library, and the results show that work discipline and job satisfaction variables have a significant influence on employee performance. Work discipline and job satisfaction are important components in improving employee performance.